Effects of field history on resistance to Bt maize by western corn rootworm, Diabrotica virgifera virgifera LeConte (Coleoptera: Chrysomelidae) - Shrestha, Ram B. (PLoS One, 2018)
Western corn rootworm, Diabrotica virgifera virgifera LeConte, has evolved resistance to transgenic maize, Zea maize L., that produces the insecticidal protein Cry3Bb1, which is derived from the bacterium Bacillus thuringiensis. We hypothesized that the level of Cry3Bb1 resistance in populations of western corn rootworm could be influenced by farming practices. To test this hypothesis, we evaluated the effect of field history on resistance to Cry3Bb1 maize by western corn rootworm. In 2013 and 2014, rootworm adults were collected from the four types of maize fields: 1) current problem fields, 2) past problem fields, 3) rotated maize fields, and 4) continuous maize fields. Those field populations along with seven Bt-susceptible control populations were tested for Cry3Bb1 resistance with both plant-based and diet-based bioassays. All field populations were resistant to Cry3Bb1 regardless of field history, however, some variation in the degree of resistance was found. For all categories of field populations, larval survivorship on Cry3Bb1 maize was significantly higher than control populations, and did not differ from survival on non-Bt maize. Evidence of resistance to Cry3Bb1 maize in plant-based bioassays was further supported by diet-based bioassays and we found a positive relationship between LC(50) values from diet-based bioassays and the larval survivorship in plant-based bioassays. This study provides evidence of Cry3Bb1 resistance throughout the agricultural landscape studied, irrespective of the field history, and highlights the need for improved resistance management approaches, such as better use of integrated pest management to better delay pest resistance.